2021
DOI: 10.21608/aasj.2021.184724
|View full text |Cite
|
Sign up to set email alerts
|

Effect of insect growth regulator, chromafenozide on the food consumption and metabolic efficiencies of the desert locust

Abstract: The objective of the current investigation was to assess the food deterrence property of chromafenozide and its impact on different food metabolic parameters of the 5 th instar nymphs of the desert locust Schistocerca gregaria. For this purpose, three doses (10, 100 and 150 µg/nymph) were topically applied (once) onto the newly molted last (5 th ) instar nymphs. chromafenozide exhibited contradictory effects on the feeding since it acted as a weak antifeedant against female nymphs only at the lowest dose but a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…For several years, investigators have investigated the factors influencing the voracity and agricultural impact of Acrididae (Pincebourde et al 2017;Dakhel et al 2020). Results showed that a wide diet spectrum and intense food consumption are considered the main factors (Basiouny and Ghoneim 2021;Egonyu et al 2021). Acrididae are known for the intestinal diversity of microbial and enzymatic capacities, and these allow the consumption and digestion of food in large quantities (Zahri et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For several years, investigators have investigated the factors influencing the voracity and agricultural impact of Acrididae (Pincebourde et al 2017;Dakhel et al 2020). Results showed that a wide diet spectrum and intense food consumption are considered the main factors (Basiouny and Ghoneim 2021;Egonyu et al 2021). Acrididae are known for the intestinal diversity of microbial and enzymatic capacities, and these allow the consumption and digestion of food in large quantities (Zahri et al 2021).…”
Section: Introductionmentioning
confidence: 99%